Mutualistic interaction between dichloromethane‐ and chloromethane‐degrading bacteria in an anaerobic mixed culture. (13th October 2017) - Chen, Gao; Kleindienst, Sara; Griffiths, Daniel R.; Mack, E. Erin; Seger, Edward S.; Löffler, Frank E.
Summary: The microbial mixed culture RM grows with dichloromethane (DCM) as the sole energy source generating acetate, methane, chloride and biomass as products. Chloromethane (CM) was not an intermediate during DCM utilization consistent with the observation that CM could not replace DCM as a growth substrate. Interestingly, cultures that received DCM and CM together degraded both compounds concomitantly. Transient hydrogen (H2 ) formation reaching a maximum concentration of 205 ± 13 ppmv was observed in cultures growing with DCM, and the addition of exogenous H2 at concentrations exceeding 3000 ppmv impeded DCM degradation. In contrast, CM degradation in culture RM had a strict requirement for H2 . Following five consecutive transfers on CM and H2, Acetobacterium 16S rRNA gene sequences dominated the culture and the DCM‐degrader Candidatus Dichloromethanomonas elyunquensis was eliminated, consistent with the observation that the culture lost the ability to degrade DCM. These findings demonstrate that culture RM harbours different populations responsible for anaerobic DCM and CM metabolism, and further imply that the DCM and CM degradation pathways are mechanistically distinct. H2 generated during DCM degradation is consumed by the hydrogenotrophic CM degrader, or may fuel other hydrogenotrophic processes, including organohalide respiration, methanogenesis and H2 /CO2 reductive acetogenesis.